BEDAQUILINE: A long but much fruitful wait since seventies - Khadka, Anjan (Medical Journal of Shree Birendra Hospital, 2015)
Tuberculosis (TB) is a major health problem in developing countries one of the leading cause of deaths due to infectious disease in the world. Drug treatment had being successful with anti-tubercular drugs available, but Multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant TB (XDR-TB) are serious forms of TB which have emerged as real concern. Bedaquiline (TMC-207 or R207910), is a new anti TB agent been approved as a part of drug regimen therapy in pulmonary MDR-TB. Bedaquiline acts on energy metabolism of the bacteria. It acts as a bactericidal drug. There are two important black box warnings for this drug, firstly prolongation of QT interval and secondly increased risk of death with bedaquiline as compared to placebo treatment. Fast track approval for bedaquiline was based on two phase 2 trials. The FDA has approved bedaquiline on Dec 2012, for the treatment of MDR-TB in adults (>18 years) as part of combination therapy under the fast track designation, priority review and orphan-product designation based on two Phase II trials. Careful use of this drug along with monitoring of the potential adverse effects and drug interactions becomes very important, as this new anti-tubercular drug has being approved after forty years, since last anti tubercular drug was approved. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.13000